2004
DOI: 10.1037/0021-9010.89.5.892
|View full text |Cite
|
Sign up to set email alerts
|

Why Does Dissimilarity Matter? Exploring Self-Categorization, Self-Enhancement, and Uncertainty Reduction.

Abstract: Although relational demographers have based their arguments on self-categorization theory, they have paid little attention to the underlying processes associated with this theory. The authors examined whether demographic dissimilarity affects individuals' identification with groups by affecting the group's prototype valence and clarity and the individual's perceptions of self-prototypicality. The data showed that the proportion of women and non-Australians in 34 work groups negatively influenced prototype vale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
96
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(104 citation statements)
references
References 36 publications
(63 reference statements)
4
96
0
4
Order By: Relevance
“…However, there is a dearth of research on the processes of social identification and categorization, which is often used to explain the effects of diversity (cf. Chattopadhyay, George, & Lawrence, 2004). Williams and O'Reilly (1998) suggested that because social categorization increases the salience of demographic categories and is the force behind the negative effects of diversity, we need to examine strategies which reduce social categorization based on demographic categories, and encourage the development of a shared team identity (Gaertner, Dovidio, Anastasio, Bachman, & Rust, 1993).…”
mentioning
confidence: 99%
“…However, there is a dearth of research on the processes of social identification and categorization, which is often used to explain the effects of diversity (cf. Chattopadhyay, George, & Lawrence, 2004). Williams and O'Reilly (1998) suggested that because social categorization increases the salience of demographic categories and is the force behind the negative effects of diversity, we need to examine strategies which reduce social categorization based on demographic categories, and encourage the development of a shared team identity (Gaertner, Dovidio, Anastasio, Bachman, & Rust, 1993).…”
mentioning
confidence: 99%
“…Although many studies on group diversity have investigated individual outcomes associated with being dissimilar to groups, the underlying processes that link dissimilarity to outcomes often have been assumed and not directly studied (Lawrence, 1997;Riordan, 2000;van Knippenberg & Schippers, 2007). A few studies have examined such mechanisms by exploring cognitive mechanisms (Phillips & Loyd, 2006;Sommers et al, 2008) or focusing on motives such as self-esteem and uncertainty reduction (Chattopadhyay et al, 2004;Goldberg et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We believe that this distinction is likely a meaningful basis for informal ethnic categorization in the research setting (i.e., a British University). Past research finds that individuals often categorize others based on "a dichotomous higherorder category, rather than multiple subcategories" (Guillaume et al, 2014(Guillaume et al, , p. 1292 because membership in different subcategories is often associated with comparable meaning such as high or low status within a context (Chattopadhyay et al, 2004; Australians and non-Australians in Australia; Joshi, Hui, & Jackson, 2006; White Americans and non-Americans in North America). In Britain, Anglo is the dominant group and thus non-Anglos in the presence of a majority Anglo participant may contrast themselves against the higher-status mainstream majority, rather than rely on finer-grained categorizations such as national or racial groups (Guillaume et al, 2014;Phinney, 1996).…”
Section: Current Studiesmentioning
confidence: 99%
See 2 more Smart Citations